Measurement of Open Flame Temperature of Nano Particle Additive Dispersed Diesel Using Digital Interferometry. Issue 10 (3rd October 2017) - Balamurugan, S.; Gayathri, B.; Sobhan, C. B.; Sajith, V.
ABSTRACT: The present work investigates the influence of ceria (CeO2 ) and its mixed oxide nanoparticles (CeZrO2 and CeZrYO2 ) dispersed in diesel on flame temperature. Interferometric technique, a non-intrusive method, has been used for the measurement of flame temperature. Optical components were aligned to obtain the wedge fringes and digital image processing techniques were used to obtain the temperature distributions from the fringes. Nanofluids (nanoparticle dispersed diesel) were prepared by dispersing CeO2, CeZrO2, and CeZrYO2 nanoparticles at various dosing levels ranging from 5 ppm to 20 ppm, using a standard ultrasonic mixing process. Results show that for concentration of nanoparticle in diesel below 10 ppm, no significant variation in flame temperature was observed as compared to pure diesel. However, above 10 ppm, the maximum temperature increases drastically, especially for 20 ppm, and is proportional to the concentration of nanoparticles. The percentage enhancement in temperature was found to be high for the mixed oxide of ceria nanoparticles, as compared to diesel with ceria nanoparticle alone, and is due to the increase in the oxygen vacancies in the ceria lattice due to doping.